2007
DOI: 10.4103/0255-0857.34770
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance in invasive and colonising <i>Streptococcus pneumoniae</i> in North India

Abstract: The present study was done to detect the antibiotic resistance in S. pneumoniae. One hundred twenty S. pneumoniae isolates from clinical specimens and 50 from nasopharyngeal sites were subjected to antimicrobial susceptibility testing by Kirby Bauer disk diffusion method and minimum inhibitory concentration (MIC) determination for penicillin and cefotaxime non-susceptible isolates. A total of 22 isolates (18.3%) from clinical sites and eight (16%) from nasopharyngeal sites showed decreased susceptibility to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 9 publications
1
36
1
Order By: Relevance
“…[11] This latest recommendation for the Þ rst time is based on the clinical syndrome and route of penicillin administration. Further, this MIC break point tends to change the earlier Þ ndings of PIRSP, published in the literature up to early 2008, to a much lower percentage for non meningitis isolates [1][2][3]5,[8][9][10] and higher percentage of complete penicillin resistance to meningitis isolates. [6,7] However, this particular study isolate antimicrobial MIC break point interpretation remains valid as it conforms to CLSI 2008 recommendation also.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…[11] This latest recommendation for the Þ rst time is based on the clinical syndrome and route of penicillin administration. Further, this MIC break point tends to change the earlier Þ ndings of PIRSP, published in the literature up to early 2008, to a much lower percentage for non meningitis isolates [1][2][3]5,[8][9][10] and higher percentage of complete penicillin resistance to meningitis isolates. [6,7] However, this particular study isolate antimicrobial MIC break point interpretation remains valid as it conforms to CLSI 2008 recommendation also.…”
Section: Discussionmentioning
confidence: 92%
“…This includes 7.3% (n = 11) isolates; [7] 15.4% (n = 2) [8] and 25% (n = 3); [9] 20% (n = 30) with 0.12 -1 µg/mL and 2 µg/mL of 26 and four respiratory isolates respectively. [10] However, in 2008, the Clinical Laboratory Standards Institute (CLSI) after re-evaluating with the more recent clinical data published new MIC penicillin break points for S. pneumoniae. [11] This latest recommendation for the Þ rst time is based on the clinical syndrome and route of penicillin administration.…”
Section: Discussionmentioning
confidence: 99%
“…Other Indian studies reported were Goyal et al, (2007) 18%, Ravi Kumar et al, (2014) 17% and Upala Devi et al, (2012 17%. In contrast, a very low resistance rate of 1.5% was reported by the invasive bacterial infection surveillance group (IBIS) from India and other authors Reba et al, (2001) 7.3%.…”
Section: Minimum Inhibitory Concentrationby Estrip Methodsmentioning
confidence: 84%
“…There is also an increase in multidrug-resistant strains. This is of major concern as it can lead to treatment failure, prolonged hospital stay, thus increasing morbidity and mortality (Goyal et al, 2007;Chawla et al, 2010 …”
mentioning
confidence: 99%
“…In a retrospective examination of serotypes and susceptibility in patients with invasive and clinically significant S. pneumoniae infections in Puducherry [8], one serotype 3 isolate was identified in a child aged <5 years and serotyping was not performed for serogroup 6 and 19 isolates. Several recent publications suggest that the incidence of antibiotic-resistant strains of S. pneumoniae is increasing in India [9][10][11]. Southeast Asian estimates of S. pneumoniae burden of disease in children aged <5 years are 2991 per 100,000 children (95% CI 2329, 3717) for invasive pneumococcal disease and 2911 per 100,000 children (95% CI 2265, 3622) for pneumonia [12].…”
Section: Discussionmentioning
confidence: 99%